Rhinophyma - the end-stage of rosacea - Katarzyna Stencel; Karina Stelmaszak; Monika Wojtasik; Aleksandra Ogiegło-Kowalczyk; Julia Samborska; Paweł Więckowiak; Michał Głodzik; Marek Miśkiewicz; Martyna Łęcka; Katarzyna Żak (Kazimierz Wielki University, 2024)
Rhinophyma is defined as a progressive, deforming, nodular enlargement of the sebaceous glands caused by hypertrophy of the sebaceous follicles. It is assumed to be the final phase of chronic rosacea occurring mainly in Caucasian men. This disease negatively affects the quality of life of patients due to decreased self-esteem and depressive disorders. Nasal deformation by narrowing the nostrils impairs the physical performance of patients and even leads to the development of sleep apnea. Treatment is mainly based on surgery to remove pathological tissue. The literature also provides the possibility of therapy using ablative techniques and laser therapy.